CONFOCAL MICROSCOPY STUDIES OF LIVING FUNGAL HYPHAE AND CONIDIA USING RHENIUM (I) TRICARBONYL COMPLEXES AS FLUORESCENT DYES - Alexander Carreño; Kamila Fernández; Felipe Sáez-Cortez; Carolina Otero; Ramiro Arratia-Pérez; Juan A. Fuentes; Rubén Polanco (Journal of the Chilean Chemical Society, 2019)
Botrytis cinerea is a ubiquitous necrotrophic filamentous fungal pathogen, causing the “grey mold” disease in a wide range of plants, including species of importance in the food industry. Recently, we reported the use of fac-[Re(I)(CO)3(2,2’-bpy)L]PF6 (C3) and fac-[Re(I)(CO)3(4,4’-dimethyl-2,2’-bpy)L]PF6 (C4) complexes as biomarkers for yeasts and bacteria. Nevertheless, the use of these complexes to stain filamentous fungi, such as Botrytis cinerea, has not been explored so far. Since Botrytis cinerea exhibits a dynamic multilayer cell wall that changes the composition during normal growth, in both their hyphae and conidia, is not possible to directly extrapolate the use of both C3 and C4 as biomarkers for Botrytis cinerea without an experimental approach. In this work, we explored new features of the luminescent compounds C3 and C4 as biomarkers for the higher filamentous fungi Botrytis cinerea, including conidia and juvenile hyphae. We found that, with the new protocol proposed, both C3 and C4 were suitable to stain conidia with a simple procedure since no cell permeabilization is required. Additionally, these results suggest that C3 and C4 can selectively stain living conidia, allowing the differentiation from non-germinating conidia. This point opens a new focus of development for rhenium (I) tricarbonyl complexes as new fluorescent biomarkers for Botrytis cinerea with potential properties as vital staining.